BUMD Contribution as a Moderation of Association Between Revenue and Expenditure with Regional Financial Independence - Vicky Dian Herdhiani; Suratno; Ardiansyah (LPPM Universitas Terbuka, 2022)
This study aims to assess and analyze local revenue, balance funds, capital expenditures, and regional financial independence with the contribution of BUMD as a moderating variable. This research uses quantitative methods with a descriptive approach. The population in this study was the District or City Government in the West Java Province of the Company in 2014-2019. The sampling technique was using the purposive sampling method. The sample in this study were districts or cities that still had a low level of independence as many as 72 sample units. Data analysis used moderate regression analysis (MRA) and Pearson correlation. The results showed that local revenue and capital expenditure had a positive correlation with regional financial independence and balance funds had a negative correlation with regional financial independence. Then the moderation regression analysis shows that the contribution of BUMD moderate negative towards regional financial independence, the contribution of BUMD results moderate positive towards regional financial independence. Meanwhile, the contribution of BUMD does not moderate the balance of funds towards regional financial independence.